2003
DOI: 10.1161/01.cir.0000091254.73351.d6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preinterventional Arterial Remodeling on Neointimal Hyperplasia After Implantation of (Non–Polymer-Encapsulated) Paclitaxel-Coated Stents

Abstract: Background-This study used serial volumetric intravascular ultrasound (IVUS) to evaluate the effect of preinterventional arterial remodeling on in-stent intimal hyperplasia (IH) after implantation of non-polymer-encapsulated paclitaxelcoated stents. Methods and Results-Patients were randomized to placebo or one of two doses of paclitaxel (low dose, 1.28 g/mm 2 ; high dose, 3.10 g/mm 2 ). Complete preinterventional, post-stent implantation, and follow-up IVUS were available in 18 low-dose and 21 high-dose patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…These proteolytic enzymes may play an important role in the outward expansion of the coronary arterial wall, 29,30 and the active biochemical reaction may lead to plaque instability and restenosis after PCI of positive remodeling lesions. 18,19,31,32 Cholesterol crystalli- zation may also be a mechanism of plaque instability in lipid-rich positive remodeling lesions. 33 The mechanism of negative remodeling is also not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteolytic enzymes may play an important role in the outward expansion of the coronary arterial wall, 29,30 and the active biochemical reaction may lead to plaque instability and restenosis after PCI of positive remodeling lesions. 18,19,31,32 Cholesterol crystalli- zation may also be a mechanism of plaque instability in lipid-rich positive remodeling lesions. 33 The mechanism of negative remodeling is also not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…If there were several MLA sites, the MLA site with the largest external elastic membrane (EEM) cross-sectional area (CSA) was chosen for evaluation. 4,[18][19][20] The proximal reference segment was defined as the segment within 10 mm of the proximal border of the entire culprit lesion and distal to any major side branch. The proximal reference site was selected from the proximal reference segment as the site with the largest lumen and least plaque burden calculated as plaque plus media divided by EEM CSA.…”
Section: Ivus Rf Data Acquisition and Analysismentioning
confidence: 99%
“…24, 25 Of note is the higher risk profile of patients/lesions enrolled in the present study as compared with the ASPECT trial, which may partially explain these differing results. The present patients had, for example, a higher rate of diabetes (31.6% vs. 7.0%) and also higher lesion complexity (ratio of B2/C lesions: 67.4% vs. 4.0%) than the subjects in that previous study.…”
Section: Discussionmentioning
confidence: 73%
“…The present patients had, for example, a higher rate of diabetes (31.6% vs. 7.0%) and also higher lesion complexity (ratio of B2/C lesions: 67.4% vs. 4.0%) than the subjects in that previous study. 24, 25 An increase in plaque area at the distal edge with subsequent reduction in LA was also clinically reflected by a higher rate of TVR at the distal edge in the PF-PES group compared to PB-PES (0% vs. 7.8%; P=0.240), which was not statistically significant due to small sample size. In any case the overall rate of TVR was higher in PF-PES than in PB-PES, indicating that lack of polymer may negatively influence neointimal response also inside the stent.…”
Section: Discussionmentioning
confidence: 96%
“…Mintz et al reported about the impact of pre-interventional arterial remodeling on NIH after implantation of non-polymerencapsulated paclitaxel-coated stents. 26 In Mintz's study, % NIH measured 18±13% in PR, 23±22% in IR, and 6±20% in NR lesions. Therefore, they concluded that drug-eluting stents may have a greater effect on reducing NIH accumulation in lesions with pre-interventional NR characteristics.…”
Section: Discussionmentioning
confidence: 91%